E. coli 6S RNA release from RNA polymerase requires σ(70) ejection by scrunching and is orchestrated by a conserved RNA hairpin - Panchapakesan, Shanker Shyam S. (Cold Spring Harbor Laboratory Press, 2012)
The 6S RNA in Escherichia coli suppresses housekeeping transcription by binding to RNA polymerase holoenzyme (core polymerase + σ(70)) under low nutrient conditions and rescues σ(70)-dependent transcription in high nutrient conditions by the synthesis of a short product RNA (pRNA) using itself as a template. Here we characterize a kinetic intermediate that arises during 6S RNA release. This state, consisting of 6S RNA and core polymerase, is related to the formation of a top-strand “release” hairpin that is conserved across the γ-proteobacteria. Deliberately slowing the intrinsic 6S RNA release rate by nucleotide feeding experiments reveals that σ(70) ejection occurs abruptly once a pRNA length of 9 nucleotides (nt) is reached. After σ(70) ejection, an additional 4 nt of pRNA synthesis is required before the 6S:pRNA complex is finally released from core polymerase. Changing the E. coli 6S RNA sequence to preclude formation of the release hairpin dramatically slows the speed of 6S RNA release but, surprisingly, does not alter the abruptness of σ(70) ejection. Rather, the pRNA size required to trigger σ(70) release increases from 9 nt to 14 nt. That a precise pRNA length is required to trigger σ(70) release either with or without a hairpin implicates an intrinsic “scrunching”-type release mechanism. We speculate that the release hairpin serves two primary functions in the γ-proteobacteria: First, its formation strips single-stranded “−10” 6S RNA interactions away from σ(70). Second, the formation of the hairpin accumulates RNA into a region of the polymerase complex previously associated with DNA scrunching, further destabilizing the 6S:pRNA:polymerase complex.